Socioculturally-Based Experience of EFL Learners: A Case Study in Kampung Inggris Pare Kediri - Musfiro .; Slamet Asari; Nirwanto Maruf (British : Jurnal Bahasa dan Sastra Inggris, 2022)
In sociocultural perspective, by participating in communities of practice and their exposure to target language, learners are able to acquire languages. It enables many educators to design ESL settings for motivating their learners. As the impact, many researchers investigated sociocultural expansion in language acquisition and learning including the role of mediation in real classroom activities. Kampung Inggris Pare is a well-known English learners’ Community that has been Vygotskian for a long time. Having more than 100 English courses and 20.000 learners, it serves EFL learners in ESL settings. Even though the investigations in Kampung Inggris Pare do not reach the mediation that occurs in social interaction outside the class. Applying a case study approach in this qualitative research, the researcher investigated social interaction between EFL learners and out-class society to capture how the out-class social interactions influence learning experience of EFL learners in Kampung Inggris Pare. Focus group discussion and semi-structured interview virtually engaged 5 respondents who came from different provinces and graduated from English courses in Kampung Inggris Pare. Then, the researcher used cross-case theme analysis that required reassembling the data based on logical connection among the themes. Findings of this study led to four dimensions of out-class society interaction in Kampung Inggris Pare including learner-roommate, learner-roomlady, learner-seller, and learner-transportation provider. Findings also highlight that the environment setting in Kampung Inggris Pare in which learners interacted within those dimensions could influence learners’ English achievement, namely linguistic knowledge such as vocabulary, grammar, and pronunciation.Keywords: socio cultural, experience, Kampung Inggris Pare